2017
DOI: 10.1161/hypertensionaha.117.09276
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-Causing Mutation in Peroxisome Proliferator–Activated Receptor γ Impairs Nuclear Export of Nuclear Factor-κB p65 in Vascular Smooth Muscle

Abstract: Selective expression of dominant negative (DN) peroxisome proliferator-activated receptor gamma (PPARγ) in vascular smooth muscle cells (SMC) results in hypertension, atherosclerosis, and increased NF-κB target gene expression. Mesenteric SMC were cultured from mice designed to conditionally express wild-type (WT) or DN-PPARγ in response to Cre-recombinase to determine how SMC PPARγ regulates expression of NF-κB-target inflammatory genes. SMC-specific overexpression of WT-PPARγ or agonist-induced activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Expression of dominant negative PPAR␥ specifically in either smooth muscle or endothelium worsens atherosclerotic lesions in apoEϪ/Ϫ mice fed a western diet, although the cell type specific mechanism may differ (808). Increased expression of inflammatory markers was a consistent observation, and a recent study showed that wild-type PPAR␥ in smooth muscle cells limits NF-B activation by facilitating nuclear export of p65 (719). Expression of PPAR␦ is increased in the vasculature of LDLrϪ/Ϫ mice infused with ANG II, and treatment with a PPAR␦ agonist attenuates vascular inflammation and atherosclerosis possibly through a suppression of ERK and p38 MAPK activation (1030).…”
Section: Athero-protective Signaling Mechanismsmentioning
confidence: 58%
“…Expression of dominant negative PPAR␥ specifically in either smooth muscle or endothelium worsens atherosclerotic lesions in apoEϪ/Ϫ mice fed a western diet, although the cell type specific mechanism may differ (808). Increased expression of inflammatory markers was a consistent observation, and a recent study showed that wild-type PPAR␥ in smooth muscle cells limits NF-B activation by facilitating nuclear export of p65 (719). Expression of PPAR␦ is increased in the vasculature of LDLrϪ/Ϫ mice infused with ANG II, and treatment with a PPAR␦ agonist attenuates vascular inflammation and atherosclerosis possibly through a suppression of ERK and p38 MAPK activation (1030).…”
Section: Athero-protective Signaling Mechanismsmentioning
confidence: 58%
“…The activated PPARγ physically associates with NFAT and blocks NFAT DNA binding and transcriptional activity in T lymphocyte (Yang et al, 2000). In SMCs, PPARγ inhibits NF-κB activity by promoting nuclear export of p65NF-κB, which is abolished by dominant-negative mutation in PPARγ1 (Mukohda et al, 2017). In SKI SMCs, overexpression of PPARγ2 or activation of PPARγ inhibits the expression of phosphorylated p65NF-κB, further confirmed the mutual negative regulation between PPARγ and NF-κB.…”
Section: Discussionmentioning
confidence: 55%
“…This hypothesis was confirmed by studies of transgenic mice, in which targeting the expression of the human hypertension-causing mutations in PPARγ selectively to either endothelium or vascular smooth muscle was done (16)(17)(18). PPARγ also was found to have antiinflammatory effects on endothelium and smooth muscle (19,20) as well as antioxidant effects on endothelium (21,22).…”
Section: Introductionmentioning
confidence: 85%
“…Western blot and IP analyses. Western blotting was performed using transfected HEK293 cells or aortic tissue as previously described (19,20). Lipofectamine (Thermo Fisher Scientific) was used to transfect HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%